Pemanfaatan Kebun Pangan Lokal untuk Meningkatkan Ketahanan Pangan Keluarga dan Mencegah Stunting: Local Food Plants Increase Food Security for Families and Prevent Stunting - Gunawan, Delima Citra Dewi; Lustiyati, Elisabeth Deta (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Stunting is a form of inhibited child growth process caused by a lack of chronic nutrient intake and recurrent infectious diseases. Consuming nutritious food is one of the keys to preventing stunting. The local food plants became one of the alternatives to getting nutritious sources of food. The purpose of dedication to this community is to empower and prosper families by conducting training on the use of local food gardens in the home market as well as the creation of local MP-ASI. The program emphasizes the empowerment efforts of families that focus on mothers as the tip of the effort to reduce stunting in the community by exploiting the outcomes of the market around the house in order to add nutritional value to the family food especially the newborn. As for Kalurahan Pandowoharjo, Kapanewon Sleman, Sleman District selected as the target location based on consideration that this area includes the focus of stunting handling in Sleman district and is a model of the village Friendly to Women and Caring for Children. As a result of dedication to this community, there has been an increase in knowledge whereas the mother's skill from the beginning did not have the skills in growing crops in the home and made the local MP-ASI to become skilled in growing food crops especially vegetables and fruits in the marketplace of the home with polybag media and also became skilled at preparing local MP-ASI by paying attention to the age, quantity, frequency, consistency and variation of food.